Memperkuat Peran Perempuan dalam Dakwah Berkemajuan di Era Digital: Strategi Pemberdayaan dan Literasi Dakwah di Organisasi Nasyiatul Aisyiyah - Rahmawati, Rahmawati; Mastorat, Mastorat; Jufrin, Jufrin; Bulqis, Bulqis (MEUSEURAYA - Jurnal Pengabdian Masyarakat, 2025)
Abstract Rapid social changes in the digital era demand more relevant, inclusive, and adaptive Islamic preaching. Preaching is now not enough to rely on conventional methods, but needs to reach the digital space as the main media for spreading Islamic values. In this context, women, especially Nasyiatul Aisyiyah cadres, have a strategic role as agents of change who are able to voice enlightening and liberating preaching messages. Based on these needs, the Bima Regency Nasyiatul Aisyiyah Regional Leadership Muballighat Training was carried out to strengthen the role of women through empowerment strategies and digital preaching literacy. This training aims to equip muballighat with theoretical understanding and practical skills in ethical and progressive digital preaching. The three main aspects emphasized are the concept of Muhammadiyah's progressive da'wah, the theory of women's empowerment in public spaces, and digital literacy for the production of moderate and educational da'wah content. The activities are designed in a participatory manner through discussions, digital content practices, and critical evaluation of Islamic narratives that develop on social media. Participants are introduced to the values ​​of tajdid, rationality, and social justice as pillars of progressive da'wah. Women are positioned as active, humanistic, and empathetic subjects of da'wah. The theory of women's empowerment emphasizes the importance of increasing self-capacity, space for expression, and access to technology as a tool for da'wah. Furthermore, digital literacy focuses on technical skills and critical thinking skills, including in sorting information, responding to hate speech, and conveying Islamic messages wisely. Keywords: Women's Empowerment in Da'wah, Islamic Digital Literacy, Progressive Da'wah Nasyiatul Aisyiyah